2004
DOI: 10.1088/0031-9155/49/4/001
|View full text |Cite
|
Sign up to set email alerts
|

In vivodetermination of prostatic zinc: phantom feasibility study

Abstract: This paper describes a phantom-based feasibility study for a potential in vivo determination of zinc in prostate, which could bring about improved diagnosis of prostate cancer. An x-ray fluorescence topographic technique was developed, which will permit determination of the Zn content in the prostate through the rectum, namely behind a 2-3 mm thick layer of the rectal wall. The topographic approach, together with a reconstruction method developed here, minimizes the interference of Zn from non-prostatic tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In this review, the feasability of measurement of Ag and As in skin has been assessed 49,50 and there has been some interesting development in the potentially useful assesment of prostate cancer by in vivo determination of Zn in the prostate. 51,52 The pollution of groundwater in West Bengal with As has been a disaster to the people living in the affected areas. Recent studies have shown, through hair and nail analysis, that nail is a good biomarker for As 75 and has indicated that other elements, such as Mn, Ni and Pb, may have been involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, the feasability of measurement of Ag and As in skin has been assessed 49,50 and there has been some interesting development in the potentially useful assesment of prostate cancer by in vivo determination of Zn in the prostate. 51,52 The pollution of groundwater in West Bengal with As has been a disaster to the people living in the affected areas. Recent studies have shown, through hair and nail analysis, that nail is a good biomarker for As 75 and has indicated that other elements, such as Mn, Ni and Pb, may have been involved.…”
Section: Discussionmentioning
confidence: 99%
“…A phantom-based feasability study was carried out by Shilstein et al 51 for the in vivo determination of Zn in prostate. Their method would allow determination through a 2-3 mm thick layer of the rectal wall using an XRF topographic technique with minimal interference from Zn in non-prostatic tissue.…”
Section: 324mentioning
confidence: 99%
“…Moreover, feasibility and in vivo studies of cadmium, mercury, gold, platinum, uranium, zinc, arsenic, etc. have been published (Börjesson et al , 1995; Christoffersson and Mattsson, 1983; Farquharson and Bradley, 1999; Jonson et al , 1985; O’Meara et al , 1997; Shakeshaft and Lillicrap, 1993; Shilstein, et al , 2004; Studinski et al , 2005). Table I summarizes elements subject to in vivo XRF.…”
Section: Elements Of Interest For In Vivo Xrfmentioning
confidence: 99%
“…Moreover, can an improved separation between prostate cancer and benign prostate hyperplasia be established? A feasibility study of a technique with an X-ray tube using mammography energies around 17 keV and zinc XRF lines at 9 keV was done by Shilstein et al (2004). The idea is to determine zinc in the prostate via a probe placed in rectum.…”
Section: Overview Of In Vivo Xrf Applications In Medicinementioning
confidence: 99%
“…Detection limits of 0.25 mg Sr g À1 Ca were obtained, which is sufficient for monitoring Sr levels in human tissues. Shilstein et al 435 presented a phantom-based feasibility study for in vivo determinations of Zn in the prostate, allowing measurements through a 2-3 mm thick layer of the rectal wall. The use of an XRF topographic technique resulted in a minimisation of the Zn interference from nonprostatic tissue.…”
Section: Clinical and Biologicalmentioning
confidence: 99%